Answer:
(x - 1)(x - 2)(x - 3).
Explanation:
f(x) = x^3 - 6x^2 + 11x - 6
f(1) = 1 - 6 + 11 - 6 = 12 - 12
= 0 so by the Factor Theorem (x - 1) is a factor.
Also, by the Rational Root theorem, as the last term is -6 and the leading coefficient is 1 some of -1, 2,-2, 3 -3, 6,-6 might be zeroes of the function.
f(-1) = -1 + 6 - 11 - 6 = -12 so -1 is not a zero and (x+ 1) is not a factor.
f(2) = 8 - 24 +22 - 6
= 30 - 30 = 0 so (x - 2) is also a factor)
Since the last term is -6 the last factor must be (x - 3)
=Checking: f(3) = 27 -6(9) + 33 - 6
= 27 - 54 + 33 - 6
= 60-60 = 0.
So the factors are (x - 1)(x - 2)(x - 3).